La gestión por procesos y la productividad de la Fábrica de mangueras ICOPLAST. - Mullo Hidalgo, Andrea Cristina (2022)
The current research project entitled "The management by processes and the productivity of the ICOPLAST hose factory" was to determine if the correct application of process management contributes to the factory's productivity. This development study of both activities and performance of the personnel and results obtained within the factory was carried out. As a result, a deficient application and control of the management by processes reflected in the losses and lack of fulfillment of the planned goals, thus increasing the dissatisfied customers and decreasing the factory's productivity constantly. Concluding that the management by processes applied correctly makes each of the operations go well obtaining a systematization of them creating an added value to their products achieving thus the expected results that reflected in their productivity.